APLIKASI BOOKING LAPANGAN FUTSAL DI AW FUTSAL DENGAN METODE FIRST COME FIRST SERVED BERBASIS WEBSITE - Moh. Rozy Setiawan; Iftitaahul Mufarrihah; Hadi Sucipto; Mahrus Ali (Fakultas Teknologi Informasi, 2025)
AW Futsal is located in Laok Jang-jang Village, Arjasa District, Sumenep Regency and provides sports fields for futsal. AW Futsal often faces customer complaints related to inadequate booking services. The main problems encountered are irrelevant information and the occurrence of double booking. Developing a webbased ordering system using the FCFS algritma is the purpose of this research to solve the problem. The FCFS algorithm prioritizes the process based on the order of arrival so that the first booker will be served first. This system is expected to increase efficiency and accuracy in the futsal field ordering process at AW Futsal, as well as improve the quality of service to customers. The calculation results from the data collected on April 21, 2024 with an average waiting time of 240 minutes from the average waiting time for field use 300 minutes from 9 bookers. Keywords: Ordering, Algorithm First Come first Served, Website